Two‐pass search strategy using accumulated band energy histogram for HMM‐based identification of perceptually identical music. Issue 2 (21st May 2013) - Myung, Jinbok; Kim, Kwang‐Ho; Park, Jeong‐sik; Koo, Myoung‐Wan; Kim, Ji‐Hwan
<x xml:space="preserve">Abstract</x> In this article, we present an efficient two‐pass search strategy for the implementation of a Hidden Markov Model (HMM)‐based music identification system. In our previous work, we demonstrated a single‐pass HMM‐based music identification system, considering its application to music copyright protection. This conventional system showed very robust performance to signal‐level variations between perceptually identical music files. However, it requires heavy computation for search. In the proposed two‐pass search system, the conventional single‐pass search is extended to two‐pass. In pass 1 of the proposed method, a queried music produces an accumulated band energy histogram which is a set of normalized sums of band energies for each frequency bin. This histogram is compared to all of the histograms for the registered music files. The system generates a list of small number of most probable music files among the all of the registered music files. In pass 2, HMM‐based search is applied only to candidate music files selected in pass 1. Using the proposed two‐pass strategy, we successfully implemented a HMM‐based music identification system, which maintains the same level robustness to signal level variations between perceptually identical music files but also produces the identification result very quickly. © 2013 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 23, 127–132, 2013